A durability optimization method for fiber Bragg grating hydrogen sensor
The preparation of fiber grating sensors through finite element simulation and magnetron sputtering instruments solves the problems of low sensitivity and electric spark risk of existing hydrogen sensors, and achieves timely and accurate monitoring of hydrogen leakage and improves sensor stability.
Patent Information
- Application Number
- CN202110552864.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-14
- Filing Date
- 2021-05-20
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-05-20
AI Technical Summary
Existing hydrogen sensors are easily affected by the external environment, which reduces sensitivity, and there is a risk of electric sparks during use, and the wiring is complex and takes up a large space, making it difficult to achieve timely and accurate monitoring of hydrogen leakage.
The optimal coating process parameters were determined through finite element simulation, a fiber grating sensor was prepared using a magnetron sputtering instrument, and hydrogen leakage was simulated in a self-built test device to verify the monitoring effect of the sensor, and optimize the coating process to improve the durability of the sensor.
It realizes timely and accurate monitoring of hydrogen leakage, improves the accuracy and response time of the sensor, reduces measurement errors, and enhances the stability and durability of the sensor.
Smart Images

Figure CN113552124B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber Bragg grating hydrogen sensors, and in particular relates to a durability optimization method for a fiber Bragg grating hydrogen sensor. Background Art
[0002] Hydrogen is a clean energy and an important chemical raw material. It is widely used in aerospace, fuel cell vehicles, metal smelting, and chemical synthesis. Since hydrogen has the smallest molecule, it is easy to leak. When the hydrogen content in the air reaches a certain level (4%-74.4% by volume), it is easy to ignite, leading to an explosion accident. Therefore, the detection of hydrogen concentration is very important. Most of the mature hydrogen sensors on the market are based on electrochemical principles. They are easily affected by the external environment and reduce the sensitivity of the sensor, resulting in measurement errors. They are also prone to generate electric sparks during use, which poses a high risk to liquid hydrogen fuel used in aerospace. In addition, the wiring is too complicated and occupies a large space.
[0003] Optical fiber sensors mainly detect through weak light signals. They have the advantages of intrinsic explosion-proof, small size, light weight, high sensitivity, corrosion resistance, anti-electromagnetic interference, and high precision. Therefore, it is of great significance to use optical fiber sensors to detect hydrogen concentration. Hill (1978) developed Bragg fiber grating (FBG) using the standing wave method; Buter (1994) coated a layer of palladium (Pd) film or multiple layers on the end face of the optical fiber to form a microlens type optical fiber hydrogen sensor; Garcia (1996) and Mandelis (1998) used the difference in laser intensity between the hydrogen sensitive surface and the reference plate to detect hydrogen; ITO (1984) proposed Pd / tungsten trioxide (WO3) as a hydrogen sensitive film structure; Tabib-Azar (1999) coated a 10-20nm thick palladium film on the surface of the multimode optical fiber to form an evanescent wave field type optical fiber hydrogen sensor; Griessen (1997) designed a guided wave optical hydrogen sensor. Sutapun et al. first reported a fiber Bragg grating hydrogen sensor; Bruic et al. sputtered a 350nm Pd film on FBG; Dai et al. polished the side of FBG and sputtered a composite film on the polished area; Caucheteur et al. used a sol-gel method to deposit composite metals on the grating area. At present, most of the research on fiber Bragg grating hydrogen sensors focuses on the effects of film thickness and coating materials on sensor performance, ignoring the effects of coating process parameters on the sensor. Summary of the invention
[0004] The purpose of the present invention is to provide a durability optimization method for a fiber Bragg grating hydrogen sensor, so as to obtain a fiber Bragg grating hydrogen sensor with high accuracy, short response time and stability, so as to enable timely and accurate monitoring of the dangerous phenomenon of hydrogen leakage. To achieve the above, the present invention adopts the following technical solutions:
[0005] A method for optimizing the durability of a fiber Bragg grating hydrogen sensor comprises the following steps:
[0006] (1) Obtaining the optimal coating process parameters:
[0007] (11) Setting and initializing a three-dimensional parameter group: the three-dimensional parameter group includes three parameters: film thickness, coating speed, and number of film layers;
[0008] (12) Establishing a simplified model of the fiber Bragg grating, the simplified model is a rectangle;
[0009] (13) meshing the simplified model to form a mesh model;
[0010] (14) Based on the birth-death unit method in ANSYS software, N hydrogen-sensitive film units are generated from left to right along the long side of the grid model; wherein N>1 and is a natural number, and the N hydrogen-sensitive film units constitute a hydrogen-sensitive film;
[0011] (15) Solving the residual stress between the hydrogen sensitive film and the fiber Bragg grating corresponding to the initial parameter group based on ANSYS software;
[0012] (16) Setting the variable parameter group: Based on the three-dimensional parameter group, assign any preset parameter to the corresponding parameter, and keep the other parameters unchanged at the initial value. Repeat steps (12) to (15) until all preset parameters are assigned;
[0013] (17) Selecting the preset parameters corresponding to the case where the residual stress distribution is uniform and the residual stress value is minimum as the optimal coating process parameters; (2) Preparing a fiber Bragg grating hydrogen sensor probe:
[0014] (21) Cleaning and air-drying the fiber Bragg grating;
[0015] (22) inserting one end of the fiber Bragg grating into one rotating shaft of the rotating stage and the other end into the other rotating shaft of the rotating stage, keeping the fiber Bragg grating taut, then placing the rotating stage in the working chamber of the magnetron sputtering apparatus, and finally connecting the two rotating shafts of the rotating stage to the driving unit in the working chamber respectively;
[0016] (23) setting the optimal coating process parameters as the working parameters of the magnetron sputtering instrument, turning on the magnetron sputtering instrument to start the driving unit in the working chamber, and then turning on the working switch on the magnetron sputtering instrument to evenly cover the Pd particles to the grating area of the fiber Bragg grating to form a fiber Bragg grating hydrogen sensor probe;
[0017] (24) The non-grating area of the fiber Bragg grating hydrogen sensor probe is connected to the tail line to obtain a fiber Bragg grating hydrogen sensor.
[0018] Preferably, in step (21), before cleaning the fiber Bragg grating, a fiber Bragg grating is first selected, and then the cladding of the non-grating region of the fiber Bragg grating is removed.
[0019] Preferably, between steps (22) and (23), the method further includes: connecting a vacuum pump to the working chamber, and connecting a nitrogen bottle to the working chamber.
[0020] Preferably, in step (23), before turning on the working switch of the magnetron sputtering instrument, the following steps are also included: when turning on the magnetron sputtering instrument, the vacuum pump is started to adjust the air pressure in the working chamber, and then the nitrogen bottle is opened to adjust the air pressure in the working chamber again.
[0021] Preferably, in step (11), L film thickness values are further added, and each film thickness value and the initial value of the coating speed and the initial value of the number of film layers in the three-dimensional parameter group form a new three-dimensional parameter group;
[0022] In step (16), after assigning the preset parameters corresponding to the three-dimensional parameter group, it further includes: based on any new three-dimensional parameter group, assigning any corresponding preset parameter to the coating speed parameter, the thin film layer number parameter and the thin film thickness parameter all keep the initial value unchanged, repeating steps (14) to (15) until the assignment of all the preset parameters of the coating speed is completed.
[0023] Preferably, after step (2), the method further comprises the following steps:
[0024] (3) Verify the detection effect of fiber Bragg grating hydrogen sensor:
[0025] (31) Arrange the verification space: Place a hydrogen tank outside a gas chamber, set a switch on the hydrogen tank, connect the hydrogen tank to the gas chamber, then place the fiber Bragg grating hydrogen sensor probe in the gas chamber, extend the tail line out of the gas chamber and connect it to the input end of a demodulator, and connect the output end of the demodulator to a display;
[0026] (32) starting the demodulator and the switch, then observing the change of the optical fiber center wavelength through the display, then recording the maximum value of the center wavelength, and finally calculating the difference between the maximum value of the center wavelength and the original center wavelength of the optical fiber, that is, obtaining the optical fiber wavelength drift;
[0027] (34) After an interval of M days, repeat step (32); where M is greater than 1 and is a natural number.
[0028] Compared with the prior art, the advantages of the present invention are as follows: first, simulation is performed based on the fiber grating film process, and the optimal coating process parameters are determined using the finite element simulation method; then, a magnetron sputtering apparatus and a fusion splicer are used to prepare the fiber grating sensor, and finally, a self-built test device is used to simulate hydrogen leakage, and the sensor monitoring effect is verified based on the sensor wavelength drift, thereby ultimately achieving the purpose of improving the durability of the sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A simplified diagram of a model of a fiber Bragg grating for growing a hydrogen-sensitive film according to an embodiment of the present invention;
[0030] Figure 2 for Figure 1 Grid division diagram;
[0031] Figure 3 (a) to (e) are the residual stress diagrams between the hydrogen-sensitive film and the fiber Bragg grating at different film thicknesses;
[0032] Figure 4 (a) ~ (b) is the film thickness - residual stress equivalent stress transformation curve;
[0033] Figure 5 (a) to (e) are comparison diagrams of coating speed-residual equivalent stress transformation curves;
[0034] Figure 6 (a) to (d) are residual stress diagrams under different numbers of film layers;
[0035] Figure 7 It is the equivalent stress transformation curve of film layer number-residual stress;
[0036] Figure 8 It is a bar graph of the durability test of fiber Bragg grating hydrogen sensors with different film thicknesses. DETAILED DESCRIPTION
[0037] The present invention will be described in more detail below in conjunction with the schematic diagram, wherein the preferred embodiment of the present invention is shown, and it should be understood that those skilled in the art can modify the present invention described herein, and still achieve the beneficial effects of the present invention. Therefore, the following description should be understood as being widely known to those skilled in the art, and not as a limitation of the present invention.
[0038] This embodiment adopts the following ideas: (1) First, simulate the fiber Bragg grating film process and use the finite element simulation method to determine the optimal coating process parameters; (2) Use a magnetron sputtering device and a fusion machine to prepare a fiber Bragg grating sensor; (3) Use a self-built test device to simulate hydrogen leakage, and verify the sensor monitoring effect based on the sensor wavelength drift.
[0039] A method for optimizing the durability of a fiber Bragg grating hydrogen sensor comprises steps (1) to (3):
[0040] (1) First, the fiber Bragg grating coating process is simulated based on ANSYS software, and finally the optimal coating process parameters are obtained.
[0041] (11) Set a three-dimensional parameter group: The three-dimensional parameter group includes three parameters: film thickness, coating speed, and number of film layers. In the three-dimensional parameter group, the values of these three parameters are constants and serve as the basic parameters for subsequent experiments. Assume that the three-dimensional parameter group is (x, y, z), x0 is the initial value of the film thickness, y0 is the initial value of the coating speed, and z0 is the initial value of the number of film layers.
[0042] (12) Establish a simplified model of the fiber Bragg grating. Specifically, the fiber Bragg grating is a rectangle when unfolded along the axis of the fiber Bragg grating, so the fiber Bragg grating is simplified to a rectangle with a length of 375 μm and a width of 125 μm. Before establishing the simplified model, the following three assumptions are made and the physical properties of the fiber Bragg grating and hydrogen-sensitive film materials are defined, as shown in Table 1. The three assumptions are as follows: (1) Regardless of the surface roughness of the fiber Bragg grating, the upper surface of the film is a plane; (2) During the finite element analysis process, the physical properties of the material remain constant; (3) The materials of the film and the fiber Bragg grating are isotropic.
[0043] Table 1 Material parameters
[0044]
[0045] That is, based on the above assumptions and physical properties, a simplified two-dimensional model is defined to study the effects of film thickness, coating speed and number of film layers on the film-fiber Bragg grating residual Mises equivalent stress.
[0046] like Figure 1 As shown, serial numbers 1 to 9 only represent the area where the 9 hydrogen-sensitive thin film units are located, and X is the width of the area, which can be set.
[0047] (13) The simplified model is meshed to form a mesh model. The units can be intelligently divided into quadrilateral units, such as Figure 2 shown.
[0048] (14) Based on the birth-and-death unit method in ANSYS software, N hydrogen-sensitive film units are generated from left to right along the long side of the grid model; where N>1 and is a natural number, and N hydrogen-sensitive film units constitute a hydrogen-sensitive film. That is, the hydrogen-sensitive film grows gradually to simulate the stress of the fiber Bragg grating during the coating process. The coating process from 1 to 9 is recorded as one coating, that is, the number of coating layers is one layer.
[0049] (15) The residual stress between the hydrogen-sensitive film and the fiber Bragg grating corresponding to the initial parameter group is solved based on ANSYS software.
[0050] (16) Setting the variable parameter group: Based on the three-dimensional parameter group, assign any preset parameter to the corresponding parameter, and keep the other parameters unchanged at the initial values. Repeat steps (12) to (15) until all preset parameters are assigned.
[0051] Specifically, the three-dimensional parameter group is (x, y, z). For example, when studying the effect of film thickness on residual stress, the values of coating speed y and number of film layers z remain unchanged, that is, they are both initial values, and the film thickness x is reassigned to the preset parameter, that is, only the value of x is changed.
[0052] Preferably, in step (11), L initial values of film thickness are further added, and each initial value of film thickness and the initial value of coating speed y0 and the initial value of film layer number z0 in the three-dimensional parameter group form a new three-dimensional parameter group; correspondingly, in step (16), after the preset parameters corresponding to the three-dimensional parameter group are assigned, it further includes: based on any new three-dimensional parameter group, any corresponding preset parameter is assigned to the coating speed parameter, and the parameters of film layer number z and film thickness x keep the initial values (z0, x0) unchanged, and repeat steps (12) to (15) until the preset parameters of all coating speeds are assigned. That is, the influence of coating speed on residual stress within the range of film thickness is further studied. That is, in each new three-dimensional parameter group, the film thickness value is a different initial value, and in the new three-dimensional parameter group, one film thickness initial value corresponds to several coating speed values (values after the assignment is completed).
[0053] (17) When the residual stress distribution is uniform and the residual stress value is minimum, the corresponding preset parameters are selected as the optimal coating process parameters.
[0054] As shown in Figure 3(a) to (e), the stress distribution in the figure is approximately the same and shows regular changes. This is because the hydrogen-sensitive film unit is gradually grown by the birth-and-death unit method, which is similar to the actual coating process. In Figure 3(a) to (b), the film thickness variable values are 60nm, 100nm, 150nm, 200nm and 250nm respectively.
[0055] As shown in Figure 4(a) to (b), the stress shows a periodic fluctuation pattern. This is because the birth and death unit method is used in the simulation process to be close to the adhesion process of the palladium film in the actual experiment. The palladium film grows step by step, and each growth process is the same, which generates periodic stress with the substrate. The role of Figure 4(a) is to select multiple film thickness values corresponding to uniform residual stress, and the role of Figure 4(b) is to select a film thickness value corresponding to the lowest uniform residual stress value.
[0056] When the film thickness is in the range of 60-150nm, the stress value shows a periodic change and a large fluctuation range. The residual stress increases with the increase of the film thickness and reaches the maximum value at 150nm. Such stress fluctuations indicate that when the film thickness is between 60-150nm, the residual stress values on the film and optical fiber surface are very unstable. When the palladium film expands due to the reaction of hydrogen, due to the uneven stress distribution, the difference between the internal stress of the film is too large, which can easily cause the film to rupture or even fall off, and the durability is low.
[0057] When the film thickness is in the range of 200-250nm, the residual stress fluctuation range is small, and the maximum value is also less than the residual stress value at a thickness of 90nm. The residual stress values on the film and optical fiber surface are relatively stable. When the palladium film expands in reaction with hydrogen, the stress distribution is relatively uniform, and the stress between the films of various parts during expansion is equivalent, so there is no possibility of the palladium film breaking or falling off due to uneven internal stress. The durability is higher than that of sensors between 60-150nm, and it is relatively stable.
[0058] As shown in Figure 5 (a) to (e): when the film thickness is in the range of 60-150nm, the coating speed has almost no effect on the fiber Bragg grating during the coating process. However, there will be an unstable residual stress value on the film and the optical fiber surface. When the palladium film (hydrogen-sensitive film) reacts with hydrogen and expands, the stress distribution is uneven and the difference between the internal stresses of the film is too large, which can easily lead to the film rupture or even shedding. When the film thickness is in the range of 200-250nm, the time required for coating a row of units (1 to 9 hydrogen-sensitive film yards) changes from 1 / 5 to 2 / 5, and the residual stress value increases significantly and produces large fluctuations. When the coating speed is 31.25um / s, there will be an unstable residual stress value on the film and the optical fiber surface. When the palladium film reacts with hydrogen and expands, the stress distribution is uneven and the difference between the internal stresses of the film is too large, which can easily lead to the film rupture or even shedding. In Figure 5 (a) to (e), the initial values of the film thickness are 60nm, 100nm, 150nm, 200nm and 250nm respectively.
[0059] Figure 6 (a) to (d), Figure 7:When the number of coating times is 1-2 times and 4 times, the residual stress values on the film and optical fiber surface are very unstable. When the palladium film expands by reacting with hydrogen, due to the uneven stress distribution, the difference between the internal stress of the film is too large, which may easily lead to the possibility of film rupture or even shedding. The equivalent stress of residual stress is most stable when the coating is divided into 3 times, and the fluctuation range is small. When the palladium film expands by reacting with hydrogen, due to the relatively uniform stress distribution, the stress between the films of each part is equivalent during expansion, and there is no rupture or shedding of the palladium film due to uneven internal stress. When the film thickness remains unchanged at 200nm, the number of coating layers is 1, 2, and 4, and the stress value decreases as the number of layers increases. In Figures 6(a) to (d), the number of coating times (number of layers) is 1, 2, 3, and 4, respectively.
[0060] As shown in Figure 3 (a) ~ (e), Figure 4 (a) ~ (b), Figure 5 (a) ~ (e), Figure 6 (a) ~ (d), Figure 7 In the figure, the horizontal axis "distance" represents the distance between the node and the origin. In order to minimize the influence of other factors on the finite element results, the data are all taken from the values at the same node. Among them, the left end of the overall model of fiber Bragg grating-hydrogen sensitive film is taken as the origin, and the "node" refers to: the stress cloud map obtained through simulation, from which the node participating in the maximum stress is selected. Because the simulation process is consistent, the model size is the same, and the length of each growth is the same, the maximum stress is consistent, and the stress value at this point is selected as the data point.
[0061] In summary, the optimal coating process parameters are: the thickness of the hydrogen-sensitive film is 200 nm, the coating speed is 62.5 μm / s, and the number of coating times is 3.
[0062] (2) Preparation of fiber Bragg grating hydrogen sensor probe
[0063] (21) First, select a FBG fiber grating, then use a wire stripper to remove the cladding of the non-grating area of the fiber grating, and then use anhydrous ethanol to clean the fiber grating and air dry it naturally. Among them, the FBG fiber grating is produced by Shenzhen Guangchi Technology Co., Ltd., with a wavelength of 1550nm and a density of 2.2g / cm 3 of transparent solid.
[0064] (22) Insert one end of the fiber Bragg grating into one rotating shaft of the rotating table, and the other end into the other rotating shaft of the rotating table, keep the fiber Bragg grating taut, then place the rotating table in the working chamber of the magnetron sputtering apparatus, and finally connect the two rotating shafts of the rotating table to the driving unit in the working chamber, connect the vacuum pump to the working chamber, and connect the nitrogen bottle to the working chamber. The above connection methods are all existing technologies and will not be described in detail here.
[0065] (23) The optimal coating process parameters are set as the working parameters of the magnetron sputtering instrument, the magnetron sputtering instrument is turned on to start the driving unit and the vacuum pump in the working chamber to adjust the gas pressure in the working chamber, and then the nitrogen bottle is opened to adjust the gas pressure in the working chamber again.
[0066] Then turn on the working switch on the magnetron sputtering instrument to evenly cover the Pd particles to the grating area of the fiber Bragg grating to form a fiber Bragg grating hydrogen sensor probe. When the magnetron sputtering instrument is working, set the current to 60mA and sputter for 10min. After the coating is completed, turn off the vacuum pump. The prepared hydrogen-sensitive film should evenly cover the entire grating area surface. The thickness of the hydrogen-sensitive film is about 200nm. The material for preparing the hydrogen-sensitive film is 99.9% pure metal palladium.
[0067] (24) Use a fusion splicer to connect the non-grating area of the fiber Bragg grating hydrogen sensor probe to the tail line to obtain a fiber Bragg grating hydrogen sensor.
[0068] (3) A fiber Bragg grating sensor capable of detecting hydrogen concentration in the air prepared according to the above preparation method was used to simulate the process of hydrogen leakage using a self-built test device, and the detection effect of the fiber Bragg grating hydrogen sensor was verified based on the sensor wavelength drift.
[0069] (31) Arrange the verification space: Place a hydrogen tank outside a gas chamber, set a switch on the hydrogen tank, connect the hydrogen tank to the gas chamber, then place the fiber Bragg grating hydrogen sensor probe in the gas chamber, extend the tail line out of the gas chamber and connect it to the input end of a demodulator, and connect the output end of the demodulator to a display;
[0070] (32) Start the demodulator and switch, that is, select the appropriate gas pressure to release hydrogen, and ensure that the slow flow rate does not affect the sensor's measurement of hydrogen concentration. Introduce 1% concentration hydrogen into the gas chamber, and after a period of time, observe the change of the optical fiber center wavelength through the display (due to the reaction between hydrogen and hydrogen-sensitive film, the center wavelength changes), then record the maximum value of the center wavelength, and finally calculate the difference between the maximum value of the center wavelength and the original center wavelength of the optical fiber (known), that is, obtain the optical fiber wavelength drift.
[0071] (34) After an interval of M days, repeat step (32); wherein M is greater than 1 and is a natural number. That is, the durability test is performed 7 days, 14 days, 21 days, and 28 days after the first measurement. The first test of the sensor wavelength drift, the hydrogen concentration is 1%, it can be seen that the sensor wavelength drift with a palladium film thickness of 200nm is above 50pm. Compared with other self-reference optical structures, the performance of this sensor is relatively stable.
[0072] like Figure 8As shown in the figure, the 50nm-150nm sensor does not achieve the expected effect in monitoring hydrogen concentration and its performance is unstable. The thickness of the sensor palladium film is between 200nm and 50nm, and the wavelength drift decreases with the decrease of thickness, which is consistent with the simulation results. A second measurement was performed one week later, and the wavelength drift generally decreased. The reason is that the palladium film is brittle, and after the reaction with hydrogen, it squeezes and ruptures each other, resulting in insufficient expansion in the secondary experiment to cause a large change in the grating area, and the drift decreases. After 14 days, it was found that the wavelength drift was relatively stable at a certain value. The reason is that the residual palladium film is broken, and there is a certain space for expansion and contraction, which is not easy to break or fall off again.
[0073] Figure 8 In the figure, 200(1) represents the first fiber Bragg grating hydrogen sensor with a film thickness of 200 nm; and so on. Figure 8 Among them, there are 4 fiber Bragg grating hydrogen sensors with a film thickness of 200nm, 2 fiber Bragg grating hydrogen sensors with a film thickness of 150nm, 1 fiber Bragg grating hydrogen sensor with a film thickness of 100nm, and 1 fiber Bragg grating hydrogen sensor with a film thickness of 50nm.
[0074] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.
Claims
1. A durability optimization method for a fiber Bragg grating hydrogen sensor, characterized in that: The following steps are involved: (1) Obtaining the optimal coating process parameters: (11) Setting and initializing a three-dimensional parameter group: the three-dimensional parameter group includes three parameters: film thickness, coating speed, and number of film layers; (12) Establish a simplified model of the fiber Bragg grating, which is a rectangle; (13) meshing the simplified model to form a mesh model; (14) Based on the birth-death unit method in ANSYS software, N hydrogen-sensitive film units are generated from left to right along the long side of the grid model; wherein N>1 and is a natural number, and the N hydrogen-sensitive film units constitute a hydrogen-sensitive film; (15) Solve the residual stress between the hydrogen-sensitive film and the fiber Bragg grating corresponding to the initial parameter group based on ANSYS software; (16) Setting variable parameter groups: Based on the three-dimensional parameter group, assign any preset parameter to the corresponding parameter, and keep the other parameters unchanged at their initial values. Repeat steps (12) to (15) until all preset parameters are assigned; (17) Selecting the preset parameters corresponding to the case where the residual stress distribution is uniform and the residual stress value is minimum as the optimal coating process parameters; (2) Preparation of fiber Bragg grating hydrogen sensor probe: (21) Cleaning and air-drying the fiber Bragg grating; (22) inserting one end of the fiber Bragg grating into one rotating shaft of the rotating stage and the other end into the other rotating shaft of the rotating stage, keeping the fiber Bragg grating taut, then placing the rotating stage in the working chamber of the magnetron sputtering apparatus, and finally connecting the two rotating shafts of the rotating stage to the driving unit in the working chamber respectively; (23) setting the optimal coating process parameters as the working parameters of the magnetron sputtering instrument, turning on the magnetron sputtering instrument to start the driving unit in the working chamber, and then turning on the working switch on the magnetron sputtering instrument to evenly cover the Pd particles to the grating area of the fiber grating to form a fiber grating hydrogen sensor probe; (24) Connecting the non-grating area of the fiber Bragg grating hydrogen sensor probe to the tail line to obtain a fiber Bragg grating hydrogen sensor; (3) Verify the detection effect of fiber Bragg grating hydrogen sensor: (31) Arrange the verification space: Place a hydrogen tank outside a gas chamber, set a switch on the hydrogen tank, connect the hydrogen tank to the gas chamber, then place the fiber grating hydrogen sensor probe in the gas chamber, extend the tail line out of the gas chamber and connect it to the input end of a demodulator, and connect the output end of the demodulator to a display; (32) Start the demodulator and switch, then observe the change of the optical fiber center wavelength through the display, then record the maximum value of the center wavelength, and finally calculate the difference between the maximum value of the center wavelength and the original center wavelength of the optical fiber, that is, obtain the optical fiber wavelength drift; (34) After an interval of M days, repeat step (32); where M is greater than 1 and is a natural number.
2. The durability optimization method of the fiber Bragg grating hydrogen sensor according to claim 1, characterized in that: In step (21), before cleaning the fiber Bragg grating, a fiber Bragg grating is first selected, and then the cladding of the non-grating area of the fiber Bragg grating is removed.
3. The durability optimization method of the fiber Bragg grating hydrogen sensor according to claim 1, characterized in that: Between steps (22) and (23), the method further includes: connecting the vacuum pump to the working chamber, and connecting the nitrogen bottle to the working chamber.
4. The durability optimization method of the fiber Bragg grating hydrogen sensor according to claim 3, characterized in that: In step (23), before turning on the working switch of the magnetron sputtering apparatus, the following steps are also included: When the magnetron sputtering instrument is turned on, the vacuum pump is started to adjust the gas pressure in the working chamber, and then the nitrogen bottle is opened to adjust the gas pressure in the working chamber again.
5. The durability optimization method of the fiber Bragg grating hydrogen sensor according to claim 1, characterized in that: In step (11), L film thickness values are further added, and each film thickness value and the initial value of the coating speed and the initial value of the number of film layers in the three-dimensional parameter group form a new three-dimensional parameter group; In step (16), after the preset parameters corresponding to the three-dimensional parameter group are assigned, the method further includes: based on any new three-dimensional parameter group, any corresponding preset parameter is assigned to the coating speed parameter, and the thin film layer number parameter and the thin film thickness parameter are kept at the initial value unchanged, and steps (14) to (15) are repeated until the preset parameters of all coating speeds are assigned.